Electronic Magazine Development in Mathematics Learning - Komarudin, Komarudin; Suherman, Suherman; Puspita, Laila; Savitri, Indy Alda (Universitas Muhammadiyah Mataram, 2020)
The purpose of this study was to develop a teaching material in the form of an electronic magazine in mathematics learning. This study uses research and development methods. The development procedure used is the ADDIE (Annalyze, Design, Development, Implementation, Evaluation) development model procedure. Data collection techniques used were observation, questionnaires and tests. The sample used was class VII SMP (Junior High School). The data analysis technique used is the t test. Based on the results of the validation carried out the media developed obtained very appropriate criteria by experts (media experts and material experts). Judging from the attractiveness of the results obtained from 2 large-scale trials and small-scale electronic magazines that were obtained obstained very interesting criteria. Based on the results of the t-test it was found that the learning outcomes of students using electronic electronic magazines were better than the learning outcomes of students who did not use mathematical electronic magazines. Based on this, it can be concluded that electrochemical magazines in mathematics learning developed can be used as mathematical learning aids.